Investigation of the mathematical model of the multidimensional mutual synchronization system - Rimas, Jonas (Lietuvos matematikos rinkinys, 1997)
The mathematical model of the mutual synchronisation system composed of 6 joined into a ring oscillators is investigated. The precise analytical expressions of the elements of the step responses matrix of the system are obtained.